Uporabnost javnomnenjskih raziskav v planiranju in načrtovanju stanovanjskih območij - Fikfak, Alenka (AR. Arhitektura, raziskave, 2003)
In the information era, public opinion has great influence since it expresses the predominant attitudes of individuals, who are well informed about a certain development and can assess their attitudes to it. The article presents a public opinion survey, which was carried out in three randomly selected multi-apartment areas built between 1945 and 1965 in Ljubljana, within the framework of the research Post-war residential estates in Slovenia methodology of evaluation and rehabilitation. The survey, as a technique of public opinion research, is an important instrument for objective definition and evaluation of developments and has to be integrated as an equally based constituent part of planning and design.
Keywords: architecture; arhitektura; Slovenia; Slovenija; Ljubljana; stanovanjska območja; stanovanjske soseske; arhitekturno načrtovanje; prenova; raziskave javnega mnenja; ankete